Impact of Chronic Liver Diseases on Specific Health-Related Quality of Life among a Sample in Babylon Governorate - Karrar G. Rasheed Al-Azzawi; Abdulkhaleq A. Ali Ghalib Al-Naqeeb; Muna A. Kadhum Zeidan (Journal of Techniques)
Patients with chronic liver disease experience a variety of symptoms with profound negative impact on health-related quality of life. Also, non-life-threatening symptoms such as fatigue, muscle and joint pain, pruritus, loss of appetite, and digestive problems can hugely decrease their quality of life and well-being. Objective: This study aims to identify most properties of the specific health related quality of life in patients suffering from (CLDs), and in order to find out the relationships among an overall evaluation of specific health related quality of life in patients with (CLDs) with some associated variables. They include but not limited to [sociodemographic characteristics]. A cross sectional study design was performed at the Gastrointestinal and Liver Diseases center in Babylon governorate, including 133 participants collected from 2nd January 2022 to 4th April 2022. There is a clear discrepancy in the level of responses for the studied domains, Specific quality of life for patients studied assigned that observed responses are mostly moderate, and they are accounted 15 (55.17%), and items of having a high-level evaluation accounted 11 (37.93%), and leftover items by having a low evaluation are accounted 2 (6.90%). According to this research findings, patients with (CLDs) have to go down regarding specific quality of life, since most studied items are accounted a moderate responding. The necessity to carry out similar further large-scale studies in different Iraqi regions in order to identify aspects of excellence and regression that progress and slow in the light of which the results of evaluating the health status related to the specific quality of life for (CLDs) patients.